Synthesis of Aryl Ketones Via Decarboxylation of Aromatic Acids Under Solvothermal Condition - Lokanatha Rai, K.M.; Suresh Babu, M.; Byrappa, K. (Asian Journal of Chemistry, 2011)
Aryl ketones were prepared by the condensation of aromatic carboxylic acids with alkyl/aryl nitrile via the decarboxylation of carboxylic acids under solvothermal condition. All the compounds were characterized by comparing with standard samples prepared by the known literature method.